2019
DOI: 10.1016/j.stemcr.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryonic Stem Cell-Derived Cardiomyocytes Regenerate the Infarcted Pig Heart but Induce Ventricular Tachyarrhythmias

Abstract: Summary Human embryonic stem cell-derived cardiomyocytes (hESC-CMs) show considerable promise for regenerating injured hearts, and we therefore tested their capacity to stably engraft in a translationally relevant preclinical model, the infarcted pig heart. Transplantation of immature hESC-CMs resulted in substantial myocardial implants within the infarct scar that matured over time, formed vascular networks with the host, and evoked minimal cellular rejection. While arrhythmias were rare in infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
243
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(301 citation statements)
references
References 22 publications
16
243
2
1
Order By: Relevance
“…The identification of multipotent CPCs has brought significant hope to the field of heart repair and further research into the early steps of CPC specification will undoubtedly lead to the design of strategies to specify multipotent CPCs into a specific mature cardiac cell type, that could then be used for cell therapy. As a recent example, hPSC-derived CMs have recently been grafted into infarcted pig hearts and showed significant engraftment, although accompanied by ventricular tachyarrhythmia (Romagnuolo et al 2019). Further improvements are thus required to successfully repair infarcted hearts in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of multipotent CPCs has brought significant hope to the field of heart repair and further research into the early steps of CPC specification will undoubtedly lead to the design of strategies to specify multipotent CPCs into a specific mature cardiac cell type, that could then be used for cell therapy. As a recent example, hPSC-derived CMs have recently been grafted into infarcted pig hearts and showed significant engraftment, although accompanied by ventricular tachyarrhythmia (Romagnuolo et al 2019). Further improvements are thus required to successfully repair infarcted hearts in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the graft-induced ventricular arrhythmias are asymptomatic up to <10 kg non-human primates, they were not tolerated in a recent study of hESC transplantation in 20-30-kg pigs, with 2/7 pigs succumbing to an arrhythmic death. 93 In that report, 1 billion hESC-CMs were surgically transplanted into pigs 3 weeks after MI, and all recipients experienced graft-induced ventricular tachyarrhythmias of worse severity than observed in non-human primates. As in previous studies, the graft-induced arrhythmias were transient and self-resolved within 1 month of transplantation.…”
Section: Contractile Mechanisms Of Benefitmentioning
confidence: 99%
“…Additionally, it has been shown that transplanted cardiomyocytes demonstrated electrical coupling with the host heart after hESC-derived cardiomyocytes were engrafted to guinea pig hearts [28]. However, several studies have also reported the development of ventricular arrhythmia within the first 2 weeks to 1 month after transplantation into a recipient's heart, which however disappeared a month after cell transplantation [31,46]. These data suggest that the arrhythmogenicity of hPSC-derived cardiomyocytes in vivo remains controversial and that it is necessary to closely monitor the heart for arrhythmias after cell transplantation in humans.…”
Section: Adverse Effects Of Cell Transplantationmentioning
confidence: 99%